Efficient Routing in Vehicular Ad-hoc Networks Using Firefly Optimization - Chhabra, Sahil (My University, 2016)
VANETs are used to provide the network environment for intelligent transportation system in which the node speed is high and topology changes frequently. So that route acquisition and nodes communications in the network are the tedious task. We can't apply the routing protocols of MANETs directly on VANETs. In this thesis work we describe an approach that is based on firefly algorithm (an implementation of swarm intelligence) to improve the routing performance in the terms of transmission time. The firefly algorithm captures the nature of fireflies i.e. how they do the task individually and how they coordinate with each other to create a system. The proposed algorithm is compared with the state-of-the art routing algorithm and it improves VANETs routing performance in terms of transmission time. The proposed algorithm applies the idea of firefly algorithm on the vehicular ad-hoc network that enhances the performance of routing by efficient packets transfer from source node to destination node.
M.Tech. Thesis
Keywords: Firefly; Transmission Time; Vanets; Intensity